2021
DOI: 10.3390/app11031018
|View full text |Cite
|
Sign up to set email alerts
|

Compact Beam Homogenizer Module with Laser-Fabricated Lens-Arrays

Abstract: We report on manufacturing of a compact beam homogenizer module including two lens arrays and an aperture. Lens arrays are fabricated by an all laser-based technology employing a precise femtosecond pulsed laser ablation and a CO2 laser polishing step. Each lens array is processed revealing a high contour accuracy and a roughness of 25 nm. The 8x8 lens arrays are designed to have a square footprint to generate a quadratic Top-Hat beam profile and focal length of 10 mm to realize compact packaging. Firstly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To obtain uniform photon flux, a beam homogenizer equipped with fly‐eye lenses and a Fourier lens was employed (Figure 3e and S8). When the original light beam from Xe lamp passed through the beam homogenizer, the photon stream was split into several small beamlets by the fly‐eye lenses, and then focused and overlapped by the Fourier lens [13] . As a consequence, light intensity gradient was eliminated in a region with a radius of 15.0 mm (the light intensity differences were less than 3 %, Figure S7), leading to a uniform radial temperature distribution of the catalyst layer as shown in the thermal image from a thermal imaging camera (Figure 3f), which was consistent with the results given by thermocouple (the y axis direction in Figure 3g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain uniform photon flux, a beam homogenizer equipped with fly‐eye lenses and a Fourier lens was employed (Figure 3e and S8). When the original light beam from Xe lamp passed through the beam homogenizer, the photon stream was split into several small beamlets by the fly‐eye lenses, and then focused and overlapped by the Fourier lens [13] . As a consequence, light intensity gradient was eliminated in a region with a radius of 15.0 mm (the light intensity differences were less than 3 %, Figure S7), leading to a uniform radial temperature distribution of the catalyst layer as shown in the thermal image from a thermal imaging camera (Figure 3f), which was consistent with the results given by thermocouple (the y axis direction in Figure 3g).…”
Section: Resultsmentioning
confidence: 99%
“…When the original light beam from Xe lamp passed through the beam homogenizer, the photon stream was split into several small beamlets by the fly-eye lenses, and then focused and overlapped by the Fourier lens. [13] As a consequence, light intensity gradient was eliminated in a region with a radius of 15.0 mm (the light intensity differences were less than 3 %, Figure S7), leading to a uniform radial temperature distribution of the…”
Section: Methodsmentioning
confidence: 99%
“…Microlens arrays with high profile accuracy and low roughness have also been successfully fabricated by this strategy ( Figure 1D ). It is also confirmed that femtosecond laser ablation combined with CO 2 laser annealing is suitable for preparing complex optical geometry ( Schwarz et al, 2020 ; Schwarz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 65%
“…While extremely complex designs achievable using additive manufacturing are out of the question [189][190][191], ablation exceeds those methods by allowing to use of glass and achieve overall size from tens of µm to mm. Optical elements, like various type lenses [192][193][194] or axicons [195], can be produced this way. In virtually all the cases additional post-processing steps are mandatory due to the necessity to smooth the surface of the structure down to optical quality (less than λ/10).…”
Section: Free-form Cutting Of Glassesmentioning
confidence: 99%
“…It gently melts the surface of the optical element, allowing surface tension to increase surface smoothness without compromising the overall shape (Figure 10). This can be induced by heating the structure to a sufficient temperature (close to the melting of the material) [196], or by employing another laser such as CO 2 [192][193][194][195]. An alternative way to achieve lenses using type III laser modification is based on the idea, of inducing very fine modifications on the surface of the material.…”
Section: Free-form Cutting Of Glassesmentioning
confidence: 99%